Clinical outcomes of vinorelbine loading CalliSpheres beads in the treatment of previously treated advanced lung cancer with progressive refractory obstructive atelectasis - Ma, Xu; Zheng, Di; Zhang, Jie; Dong, Yu; Li, Lingling; Jie, Bing; Jiang, Sen (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Drug-eluting beads bronchial arterial chemoembolization (DEB-BACE) has been used in the treatment of locally advanced lung cancer and has the potential to improve outcomes and reduce recurrence. However, DEB-BACE shows a poor therapeutic effect in advanced lung cancer after failure of multiple therapies. This study assessed the effect of DEB-BACE in the treatment of progressive lung cancer with refractory obstructive atelectasis. Methods: Progressive advanced lung cancer patients with refractory obstructive atelectasis were voluntarily enrolled in this study after failure of multiple conventional therapies. Baseline information, DEB-BACE treatment process, and changes in clinical symptoms were recorded. The primary endpoints were the objective response rate (ORR) and improvement rate of dyspnea. The secondary endpoints were time-to-progression (TTP), overall survival (OS), and rate of pulmonary re-expansion. Treatment-related adverse events and serious adverse events were analyzed to assess the safety of DEB-BACE. The Cox regression model was performed to analyze the possible factors impacting prognosis of DEB-BACE. Results: DEB-BACE was successfully performed with CalliSpheres beads loaded with vinorelbine in the 20 enrolled patients. ORR and disease control rate were 80% and 85%, respectively, at the first follow-up (43.4±15.26 days). The improvement rate of dyspnea was 85% and 80% at 1 week and 1 month (P<0.0001, P<0.0001), respectively. TTP was 41.25±14.43 days and 89.55±61.7 days before and after DEB-BACE, respectively; DEB-BACE delayed the progression of advanced lung cancer (P<0.0001). OS was 238.03±33.74 days (95% confidence interval: 171.9–304.16). The rate of pulmonary re-expansion was 80% at the first follow-up. The reasons for poor prognosis were tumor necrosis, longer disease duration, and pulmonary atelectasis duration (P=0.012, P=0.038, P=0.029). Massive hemoptysis was observed in two cases, and one patient died of asphyxia caused by hemoptysis. Moderate hemoptysis occurred in one case. All three adverse events were considered as the result of the tumor cavity after DEB-BACE. Conclusion: DEB-BACE loaded with vinorelbine is a feasible option for progressive advanced lung cancer with obstructive atelectasis after failure of other treatments.